pharmacokinetics and pharmacodynamics of prasugrel in healthy Chinese, Japanese, and Korean subjects compared with healthy Caucasian subjects - Small, David S; Kothare, Prajakti; Yuen, Eunice; Lachno, D. Richard; Li, Ying G; Winters, Kenneth J; Farid, Nagy A; Ni, Lan; Jakubowski, Joseph A; Salazar, Daniel E; Thieu, Vivian T; Payne, Christopher D (European journal of clinical pharmacology, 2010)
Purpose Prasugrel is a novel thienopyridine prodrug metabolised to an active metabolite that binds irreversibly to the platelet P2Y₁₂ receptor and inhibits adenosine diphosphate (ADP)-induced platelet aggregation. We compared prasugrel pharmacokinetics, pharmacodynamics, and tolerability in healthy Chinese, Japanese, Korean and Caucasian subjects. Methods In an open-label, single-centre, parallel-design study, 89 healthy subjects (25 Chinese, 20 Japanese, 22 Korean and 22 Caucasian) aged 20-65 years were given a prasugrel 60-mg loading dose (LD) followed by daily 10-mg maintenance doses (MD) for 7 days and then 5-mg MD for 10 days. Plasma concentrations of prasugrel's active metabolite and inhibition of ADP-induced platelet aggregation (IPA) were determined. Results Mean exposure to prasugrel's active metabolite in all treatment regimens was higher in each of the Asian groups than in the Caucasian group, although there was considerable overlap between individual exposure estimates in Asians and Caucasians. The mean IPA was also higher in Asians than in Caucasians following a prasugrel 60-mg LD, although the difference did not consistently achieve statistical significance. Prasugrel 10-mg or 5-mg MD produced statistically significantly higher IPA in each Asian group compared with that in the Caucasians. Prasugrel was well tolerated during the LD and MD regimens by all groups. Conclusions Mean exposure to the prasugrel active metabolite following prasugrel 60-mg LD and during daily 10-mg or 5-mg MD was higher in each of the Asian groups than in the Caucasian group, which resulted in greater platelet inhibition.